Sequential injection spectrophotometric determination of tetracycline antibiotics in pharmaceutical preparations and their residues in honey and milk samples using yttrium (III) and cationic surfactant - Thanasarakhan W. (2014)
A sequential injection analysis (SIA) spectrophotometric method for determining tetracycline (TC), chlortetracycline (CTC) and oxytetracycline (OTC) in different sample matrices were described. The method was based on the reaction between tetracyclines and yttrium (III) in weak basic micellar medium, yielding the light yellow complexes, which were monitored at 390, 392 and 395 nm, respectively. A cationic surfactant, cetyltrimethylammonium bromide (CTAB) was used to obtain the micellar system. The linear ranges of calibration graphs were between 1.0 × 10-5 and 4 × 10-4 mol L-1, respectively. The molar absorptivities were 5.24 × 10 5, 4.98 × 104 and 4.78 × 104 L mol-1 cm-1. The detection limits (3σ) were between 4.9 × 10-6 and 7.8 × 10-6 mol L-1 whereas the limit of quantitations (10σ) were between 1.63 × 10 -5 and 2.60 × 10-5 mol L-1 the interday and intraday precisions within a weak revealed as the relative standard deviations (R.S.D., n = 11) were less than 4%. The method was rapid with a sampling rate of over 60 samples h-1 for the three drugs. The proposed method has been satisfactorily applied for the determination of tetracycline and its derivatives in pharmaceutical preparations together with their residues in milk and honey samples collected in Chiang Mai Province. The accuracy was found to be high as the Student's t-values were found to be less than the theoretical ones. The results were compared favorably with those obtained by the conventional spectrophotometric method. © 2011 Elsevier B.V. All rights reserved.